Determination of 2-alkylcyclobutanones in ultraviolet light-irradiated fatty acids, triglycerides, corn oil, and pork samples: Identifying a new source of 2-alkylcyclobutanones. (15th February 2017) - Meng, Xiangpeng; Chan, Wan
Highlights: 2-Alkylcyclobutanones are used as markers to identify foods irradiated with ionizing irradiation. We tested the uniqueness of 2-dodecylcyclobutanone for irradiated food determination. The analyses identified 2-alkylcyclobutanones in UVC-irradiated food for the first time. Multiple analytical methods were used to validate the identifications. Dose-dependent formation of 2-alkylcyclobutanones in UV-irradiated food was observed. Abstract: Previous studies have established that 2-alkylcyclobutanones (2-ACBs) are unique radiolytic products in lipid-containing foods that could only be formed through exposure to ionizing radiation, but not by any other means of physical/heat treatment methods. Therefore, 2-ACBs are currently the marker molecules required by the European Committee for Standardization to be used to identify foods irradiated with ionizing irradiation. Using a spectrum of state-of-the-art analytical instruments, we present in this study for the first time that the generation of 2-ACBs was also possible when fatty acids and triglycerides are exposed to a non-ionizing, short-wavelength ultraviolet (UV-C) light source. An irradiation dosage-dependent formation of 2-ACBs was also observed in UV-C irradiated fatty acids, triglycerides, corn oil, and pork samples. With UV-C irradiation becoming an increasingly common food treatment procedure, it is anticipated that the results from this study will alert food scientists and regulatory officials to a potential new source for 2-ACBs.